2021
DOI: 10.1002/jee.20441
|View full text |Cite
|
Sign up to set email alerts
|

The honeycomb of engineering framework: Philosophy of engineering guiding precollege engineering education

Abstract: Background: Understanding the nature of engineering is important for shaping engineering education, especially precollege education. While much research has established the pedagogical benefits of teaching engineering in kindergarten through 12th grade (K-12), the philosophical foundations of engineering remain under-examined.Purpose: This conceptual paper introduces the honeycomb of engineering framework, which offers an epistemologically justified theoretical position and a pedagogical lens that can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 96 publications
(97 reference statements)
0
19
0
Order By: Relevance
“…The authors argued that applying a situated perspective on engineering learning could also shape research on engineering education and allow for significant contributions to advance our understanding of learning. Through our review of these studies and the emerging body of scholarship devoted to integrating the STEM disciplines (e.g., Bryan et al, 2015; Moore et al, 2014; NAE/NRC, 2014; Purzer et al, 2022), we synthesized five distinguishing characteristics of integrated STEM education. These five characteristics guided our design of integrated STEM instruction and curriculum development in this study and are summarized below [adapted from Bryan et al, 2015]: The content and practices of one or more anchor STEM disciplines define the primary learning goals : Anchor disciplines are the fundamental disciplines from which the primary learning goals for instruction are derived.…”
Section: Theoretical Framework and Relevant Prior Researchmentioning
confidence: 99%
“…The authors argued that applying a situated perspective on engineering learning could also shape research on engineering education and allow for significant contributions to advance our understanding of learning. Through our review of these studies and the emerging body of scholarship devoted to integrating the STEM disciplines (e.g., Bryan et al, 2015; Moore et al, 2014; NAE/NRC, 2014; Purzer et al, 2022), we synthesized five distinguishing characteristics of integrated STEM education. These five characteristics guided our design of integrated STEM instruction and curriculum development in this study and are summarized below [adapted from Bryan et al, 2015]: The content and practices of one or more anchor STEM disciplines define the primary learning goals : Anchor disciplines are the fundamental disciplines from which the primary learning goals for instruction are derived.…”
Section: Theoretical Framework and Relevant Prior Researchmentioning
confidence: 99%
“…In our research we observed that many engineers, perhaps most, have difficulty explaining how their work creates economic and social value [3]. This inspired a series of studies to understand how engineers generate significant economic and social value from routine activities that do not necessarily require innovation [4], complementing existing entrepreneurship models [5].…”
Section: Engineering Practice and Engineering Value Generationmentioning
confidence: 92%
“…We first suggest that engineering schools help students learn from research-based explanations on how they will contribute economic and social value as engineers as outlined in this paper. This can help rebuild awareness on the critical nexus between technical engineering and economics [5]. This could be reinforced by helping faculty staff understand how their work contributes economic and social benefits, so that they can, in turn, better inform students on how their classroom learning will contribute to practice.…”
Section: Suggestions For Actionmentioning
confidence: 99%
“…Looking ahead, the question is how this aspect of the NOE might be taught in in the context of precollege engineering instruction. Perhaps this could be done by taking a “reverse engineering” approach (Purzer et al, 2022 ). For instance, students might examine the products created by a company that claims to value sustainability.…”
Section: Moving Noe Research Forwardmentioning
confidence: 99%